on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s} OF
by UNIVERSITY
Fractals, Vol. 25, No. 3 (2017) 1750033 ( 16 pages) c World Scientiﬁc Publishing Company DOI: 10.1142/S0218348X17500335
ON HADAMARD FRACTIONAL CALCULUS
LI MA ^{∗} and CHANGPIN LI ^{†} Department of Mathematics, Shanghai University Shanghai 200444, P. R. China ^{∗} mali20062787@163.com ^{†} lcp@shu.edu.cn
Received January 8, 2017 Accepted March 29, 2017 Published May 11, 2017
Abstract
This paper is devoted to the investigation of the Hadamard fractional calculus in three aspects. First, we study the semigroup and reciprocal properties of the Hadamardtype fractional oper ators. Then, the deﬁnite conditions of certain class of Hadamardtype fractional diﬀerential equations (HTFDEs) are proposed through the Banach contraction mapping principle. Finally, we prove a novel Gronwall inequality with weak singularity and analyze the dependence of solu tions of HTFDEs on the derivative order and the perturbation terms along with the proposed initial value conditions. The illustrative examples are presented as well.
Keywords: HadamardType Fractional Operators; Semigroup; WellPosedness; Banach Con traction Mapping Principle; Perturbation.
1. INTRODUCTION
Recently, a large amount of interest in fractional calculus has been stimulated due to its various applications, especially in diﬀerent realms of applied sciences like physics, mechanics, engineering, and biology, see Refs. 1–12 and references therein.
^{†} Corresponding author.
So far, there have existed several deﬁnitions of frac tional integrals and fractional derivatives, such as Gr¨unwald–Letnikov, Riemann–Liouville, Caputo, Riesz, Erd´elyi–Kober, and Hadamard, integrals and/or derivatives. ^{2}^{,}^{1}^{3}^{–}^{1}^{7} Generally speaking, they are not equivalent ^{2}^{,}^{4} and have their respective
17500331
on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s} OF
by UNIVERSITY
L. Ma & C. P. Li
backgrounds. ^{1}^{8}^{–}^{2}^{0} To the best of our knowledge, most of publications focus on the fractional dif ferential equations involved Riemann–Liouville and Caputo derivatives. ^{2}^{1}^{–}^{2}^{3} However, there are still some of the articles discussing the properties of Hadamard version. For example, in Ref. 24, the authors list the main two diﬀerences between the Hadamard fractional derivative and the Riemann–
Liouville fractional derivative. Overall, on one hand, the kernel of the Hadamard fractional integral takes the logarithmic form of log( ^{x} ) instead of the form of (x − t). On the other hand, the Hadamard frac tional derivative can be regarded as generalization
t
operator (x _{d}_{x} ) ^{n} , whose construction is well
suited to the case of the halfaxis and is invariant relative to dilation, while the Riemann–Liouville fractional derivative can be viewed as an extension of the classic diﬀerential operator ( _{d}_{x} ) ^{n} cursorily.
In this paper, we investigate Hadamard fractional calculus, including Hadamard fractional integrals and Hadamard fractional derivatives, Hadamard type fractional integrals, and Hadamardtype frac tional derivatives, which have slight diﬀerences but are unitedly called Hadamard fractional calculus. How to determine the deﬁnite conditions for frac tional diﬀerential equations seems to be a ticklish matter. ^{2}^{5} It is worth mentioning that the studies of the deﬁnite conditions for fractional diﬀerential equations have been more or less mentioned. ^{2}^{4}^{,}^{2}^{6}^{–}^{3}^{1} Delbosco and Rodino show ^{3}^{2} the existence and uniqueness for a nonlinear Riemann–Liouville type fractional diﬀerential equation. In Ref. 33, the authors discuss the wellposed conditions for a cer tain class of fractional order boundary value prob lems with Caputo derivatives. There are few stud ies on deﬁnite conditions of Hadamard fractional diﬀerential equations (HFDEs) and Hadamardtype fractional diﬀerential equations (HTFDEs). In this paper, we consider such questions. In addition, it is remarked that memory depen dency of solutions is a desired property in frac tional diﬀerential equations. So this motivates us to detect the parameter dependence of the solutions of HFDEs and HTFDEs. The rest of the paper is organized as fol lows: In Sec. 2, we introduce some deﬁnitions of Hadamardtype fractional integral and derivative along with the associate function spaces. In Sec. 3, we discuss semigroup and reciprocal properties of Hadamardtype fractional integral and derivative operators. Section 4 is dedicated to investigating
of the
d
d
the wellposedness. In addition, Sec. 5 deals with the continuous dependence of parameters. The last section concludes this paper.
2. PRELIMINARIES
In this section, we mainly present some basic deﬁni tions, function spaces, and properties related to the Hadamardtype fractional integral and fractional derivative. First of all, let f (x) be a function deﬁned on (a, b), where 0 ≤ a<b ≤ ∞ and µ ∈ R.
Deﬁnition 1. The Hadamardtype fractional inte gral with parameter µ ∈ R (Hadamardtype inte gral for brevity) of the given f (x) with order α > 0 is deﬁned as ^{1}^{4}^{,}^{1}^{5}
H D
−α
a
_{,}
^{+}
_{µ} f(x) =
Γ(α) x
1
a
x µ
t
× log ^{x} ^{α}^{−}^{1} f(t) ^{d}^{t} ,
t
t
(1)
where x ∈ (a, b), and 0 ≤ a<b ≤ ∞.
Deﬁnition 2. The Hadamardtype fractional derivative with parameter µ ∈ R (Hadamardtype derivative for brevity) of the given f (x) is deﬁned
_{a}_{s} 14,15
(2)
where δ = x _{d}_{x} , n − 1 < α ≤ n ∈ Z ^{+} , x ∈ (a, b), and 0 ≤ a<b ≤ ∞.
If letting µ = 0, Deﬁnitions 1 and 2 are just the usual Hadamard integral and derivative, respec tively. Hadamard fractional calculus always repre sents Hadamard(type) integral and derivative in this paper if no confusion arises.
Deﬁnition 3. The singleparameter Mittag–Leﬄer function and the twoparameter Mittag–Leﬄer function are deﬁned as ^{2}
H D
_{+} _{,} _{µ} f(x) = x ^{−}^{µ} δ ^{n} x ^{µ} ( _{H} D
α
a
d
−(n−α) a ^{+} , µ
f (x)),
E _{α} (x) =
∞
k=0
x ^{k}
Γ(αk
_{+} _{1}_{)} ,α> 0
and
E _{α}_{,} _{β} (x) =
respectively.
∞
k=0
x ^{k}
Γ(αk
_{+} _{β}_{)} ,α> 0,β> 0,
Obviously,
E _{α}_{,} _{1} (x) = E _{α} (x),
E _{1} (x) = E _{1}_{,} _{1} (x) = e ^{x} .
In the sequel, for the Hadamardtype frac tional integral operator _{H} D _{a}_{+}_{,} _{µ} (·), we deﬁne space
−α
17500332
on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
OF
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s}
by UNIVERSITY
On Hadamard Fractional Calculus
X
Lebesgue measurable functions f on [a, b] for which
(a, b) (c ∈ R, 1 ≤ p ≤ ∞) of those realvalued
p
c
f _{X}
p
c
< ∞, where
f _{X}
p
c
= _{b}
a
t ^{c} f(t) ^{p} ^{d}^{t}
t
1/p
,
(1 ≤ p < ∞, c ∈ R)
(3)
and
f _{X}
∞
c
=
ess sup _{a}_{≤}_{t}_{≤}_{b} [t ^{c} f (t)], (c ∈ R).
(4)
(a, b)
In particular, if c = 1/p, then the space X coincides with the common L ^{p} (a, b) space.
Then, for the Hadamardtype fractional dif
ferentiation operator _{H} D _{a}_{+}_{,} _{µ} (·), we deﬁne space
AC
p
c
α
n
δ;
_{µ} [a, b] of those functions satisfying
n
δ;
AC
_{µ} [a, b] = g : [a, b] →
Rδ ^{n}^{−}^{1} (x ^{µ} g(x))
∈
AC[a, b], µ ∈ R; δ = x _{d}_{x} ,
d
(5)
where AC[a, b] is the set of absolutely continu
ous functions on [a, b]. In particular, if µ = 0,
AC ^{n} _{0} [a, b] ≡ AC ^{n} [a, b].
δ;
δ
Next, we construct the generalized weighted space C _{µ}_{,} _{γ}_{,} _{l}_{o}_{g} [a, b] deﬁned as
C _{µ}_{,} _{γ}_{,} _{l}_{o}_{g} [a, b] = f(x) log ^{x} ^{γ} x ^{µ} f(x)
a
∈ C[a, b], f _{C} _{µ}_{,} _{γ}_{,} _{l}_{o}_{g}
=
_{} log ^{x} ^{γ} x ^{µ} f(x) _{} _{C} .
a
(6)
Obviously, C 0, γ, log [a, b] ≡ C γ, log [a, b], C 0, 0, log [a, b] ≡ C[a, b]. In other words, the generalized weighted space C _{µ}_{,} _{γ}_{,} _{l}_{o}_{g} [a, b] can be regarded as an extension of weighted space C _{γ}_{,} _{l}_{o}_{g} [a, b], which can be found in Refs. 2 and 24. In the following, we give the fundamental proper ties for the Hadamard(type) fractional operators.
Lemma 1 (see Ref. 2 ). Let α > 0,β > 0, 1 ≤
p ≤ ∞, 0 ≤ a<b ≤ ∞ and let µ, c ∈ R with µ ≥ c.
(a, b) the semigroup property holds,
Then for f ∈ X i.e.
p
c
H D
−α
a ^{+} , µ ^{H} ^{D} a ^{+}
−β
_{,}
_{µ} f(x) = _{H} D
−(α+β) a ^{+} , µ
f (x).
(7)
Lemma 2 (see Ref. 2 ). Let α ≥ β > 0, 1 ≤ p ≤ ∞, 0 ≤ a<b ≤ ∞ and let µ, c ∈ R with µ ≥ c.
Then for f ∈ X
p
c
(a, b) there holds
H
D
β
a ^{+} , µ ^{H} ^{D} a ^{+}
−α
_{,}
_{µ} f(x) = _{H} D
−(α−β) a ^{+} , µ
f (x).
(8)
In particular, if β = m ∈ Z ^{+} , then
H
D
m
a ^{+} , µ H ^{D} a ^{+}
−α
_{,}
_{µ} f(x) = _{H} D
−(α−m) a ^{+} , µ
f (x).
(9)
Lemma 3 (see Ref. 2). If 0 <α< 1, f (x) ∈
L(a, b), and _{H} D
−(1−α)
a
1
f (x) ∈ AC
δ
[a, b], then
^{+}
H
_{D} −α
a
^{+}
H
_{+} f(x) = f(x) + c log ^{x} ^{α}^{−}^{1} ,
D ^{α}
a
a
(10)
where c is a constant associated with some initial value.
Lemma 4 (see Ref. 2). If 0 <α< 1, f (x) ∈ L(a, b), then the relation _{H} D ^{α} _{+} f (x)=0 valids, if and only if,
a
f(x) = c log ^{x} ^{α}^{−}^{1} ,
a
(11)
where c is an arbitrary real number.
Motivated by the above two lemmas for Hada mard fractional diﬀerentiation operator _{H} D ^{α} _{+} (·), it is trivial to obtain analogous conclusions for Hadamardtype diﬀerentiation operator _{H} D
(·) as follows:
a ^{+} , µ
a
α
Lemma 5.
H D
−(1−α)
a ^{+} , µ
f
If 0
<α< 1, f (x)
1
(x) ∈ AC _{δ}_{;} _{µ} [a, b], then
∈
L(a, b), and
H D
−α
a ^{+} , µ ^{H} ^{D} a
α
_{+} _{,} _{µ} f (x) = f (x) + cx ^{−}^{µ} log ^{x}
a
^{} α−1 ,
(12)
where c is a constant associated with some initial value.
≥ 1 − α and f (x) ∈
C _{µ}_{,} _{γ}_{,} _{l}_{o}_{g} [a, b], then the relation _{H} D ^{α} _{+} _{,} _{µ} f(x)=0
valids, if and only if,
Lemma 6. If 0 <α< 1, γ
a
f (x) = cx ^{−}^{µ} log ^{x} ^{α}^{−}^{1} ,
a
(13)
where c is an arbitrary real number.
Based on Ref. 34, we introduce the following two lemmas.
Lemma 7. If p ≥ 1
and a, b ≥ 0, then
(a + b) ^{p} ≤ 2 ^{p}^{−}^{1} (a ^{p} + b ^{p} ).
(14)
17500333
on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s} OF
by UNIVERSITY
L. Ma & C. P. Li
Lemma 8 (H¨older inequality). Let p > 1 and q satisﬁes _{p} + ^{1} _{q} = 1. If u(t) ∈ L ^{p} (a, b) and v(t) ∈ L ^{q} (a, b), then u(t)v(t) ∈ L(a, b), and
1
^{} t
a
u(τ)v(τ)dτ ≤ u _{p} v _{q} ,
(15)
where t ∈ (a, b].
Next, we present the inequality which has been proved in Ref. 30.
Lemma 9.
we have
log
If λ, υ, ω > 0, then for any t > a, a > 0,
a ^{} 1−υ ^{} _{t}
t
a
log _{s} υ−1 log
t
×
s ^{} −ω ds
a
s
≤
Cω ^{−}^{λ} ,
a ^{} λ−1
s
(16)
where C = max{1, 2 ^{1}^{−}^{υ} }Γ(λ)(1 + λ(λ + 1)/υ).
The following Beesack inequality can be found in Refs. 35 and 36.
Lemma 10 (Beesack inequality). Let a(t), q(t) ∈ L(a, b), u(t) and b(t) be real valued contin uous functions on [a, b], and b(t), q(t) are both non negative functions, satisfying
u(t) ≤ a(t) + q(t)
a
t
b(τ )u(τ )dτ,
∀ t ∈ [a, b],
(17)
then we have
u(t) ≤ a(t) + q(t)
a
t
a(τ)b(τ)
× exp
τ
t
q(s)b(s)ds dτ.
(18)
Remark 1. Furthermore, if u(t) satisﬁes the same conditions as Lemma 10, and suppose that a(t), q(t) are both continuous on [a, b], then we have the fol lowing inequality:
u(t) ≤ a(t)
+ q(t)
1 − ρ t
1
a
a(s)b(s)ds ,
(19)
b
where ρ = ^{}
a
q(s)b(s)ds < 1 is demanded, which
has been proved in Ref. 37.
3. SEMIGROUP AND RECIPROCAL PROPERTIES OF HADAMARDTYPE FRACTIONAL INTEGRAL AND DERIVATIVE
In this section, we address some basic properties, for instance, semigroup and reciprocal properties on Hadamardtype fractional operators as follows:
Lemma 11. (I) For Hadamardtype fractional inte gral (1), if α → 1, then we obtain
H D
−α
a
_{,}
^{+}
_{µ} f(x) =
a
x
_{x} µ f(t) ^{d}^{t} .
t
t
(20)
Moreover, as α → 0 ^{+} , we have
(21)
(II) For Hadamardtype fractional derivative (2),
H
D
_{,} _{µ} f (x) = f (x).
−α
a
^{+}
if α → 0 ^{+} , then we have
H
D
_{+} _{,} _{µ} f (x) = f (x).
α
a
If α → (n − 1) ^{+} , then
H D
a α _{+} _{,} _{µ} f(x) =
x ^{−}^{µ} δ ^{n}^{−}^{1} (x ^{µ} f (x))
(22)
where δ = x
d
dx
^{.} If α → n ^{−} , we have
(δ + µ) ^{n}^{−}^{1} f (x),
(23)
H D
α _{+} _{,} _{µ} f(x)
a
= x ^{−}^{µ} δ ^{n} (x ^{µ} f (x)) (δ + µ) ^{n} f(x),
(24)
where δ = x ^{d}
dx ^{.} In particular, as α → 1, then
H D
a α _{+} _{,} _{µ} f (x) = µf (x) + xf ^{} (x)
(δ + µ)f(x).
(25)
In view of the deﬁnition of Hadamardtype
fractional integral (1), it is easy to formulate case α = 1. For (21), we can use integration by parts as
follows.
Proof.
lim
α→0
+
^{H} ^{D}
−α
a
_{,}
^{+}
_{µ} f(x)
=
=
lim
α→0 ^{+}
lim
α→0 ^{+}
Γ(α)
1
a
x
_{x} µ log ^{x} ^{α}^{−}^{1} f(t) ^{d}^{t}
t
t
t
Γ(1 + α)
−1
t
_{x} µ f(t) log ^{x}
t
^{} α ^{}
x
a
− ^{x} log ^{x}
t
a
_{} _{α} d _{t}
_{x} µ f(t) = f(x).
(26)
17500334
on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s} OF
by UNIVERSITY
For case (II), combining (2), we can easily get
lim
α→0
+
^{H} ^{D}
_{+} _{,} _{µ} f(x)
α
a
=
+ _{x} −µ ^{} _{x}
lim
α→0
dx ^{x} µ Γ(1 − α) x
d
1
a
×
log ^{x} ^{−}^{α} f(t) ^{d}^{t}
t
t
_{=} _{x} −µ+1 ^{d}^{(}
x
t ^{µ} f(t) ^{d}^{t} )
a
t
_{d}_{x}
= f (x).
x µ
t
(27)
The proofs of other cases for this lemma can be similarly obtained, so we omit them here. The proof is thus completed.
Lemma 12. If 0 <α< 1 and β > 0, then the following relations hold.
H D
H D
a ^{+} _{,} _{µ} x ^{−}^{µ} log
−α
^{x}
a
^{} β−1 ^{}
Γ(β)
_{α}_{)} x ^{−}^{µ} log ^{x} ^{β}^{+}^{α}^{−}^{1}
_{=}
Γ(β +
a
α
a
_{+}
_{,} _{µ} x ^{−}^{µ} log
^{x}
a
^{} β−1 ^{}
Γ(β)
_{α}_{)} x ^{−}^{µ} log ^{x} ^{β}^{−}^{α}^{−}^{1}
_{=}
Γ(β −
a
,
.
(28)
(29)
Proof.
H D
First we prove (28). Based on (1), we have
_{,} _{µ} x ^{−}^{µ} log ^{x}
a
−α
a
^{+}
^{} β−1 ^{}
=
Γ(α) x
x
−µ
a
log ^{x} ^{α}^{−}^{1} log
t
a ^{} β−1 _{d}_{t}
t
t
_{=} x ^{−}^{µ} (log ^{x} Γ(α)
_{)}
β+α−1
a
^{} 1
0
(1 − y) ^{α}^{−}^{1} y ^{β}^{−}^{1} dy
_{=}
Γ(β)
_{α}_{)} x ^{−}^{µ} log ^{x} ^{β}^{+}^{α}^{−}^{1} ,
a
Γ(β +
(30)
where the inner integral term is evaluated by the
and by using
the relation between the Beta function and Gamma function. After a few calculations, we can obtain
formula (29) by utilizing (2) and (28). Thus, we ﬁnish this proof.
change of variable y = log _{a} / log ^{x}
t
_{a}
Remark 2. For Hadamard fractional integral and derivative, we have analogue conclusions which can be considered as µ = 0 in Lemmas 11 and 12, respectively.
On Hadamard Fractional Calculus
Moreover, motivated by Lemma 2, for 0 <α<β, we have the following two conclusions:
Let n − 1 <α<β ≤ n ∈ Z ^{+} ,1 ≤ p ≤
∞, 0 ≤ a<b ≤ ∞ and let µ, c ∈ R, such that µ ≥ c.
Then for f ∈ X there holds
b]
Theorem 1.
p
c
(a, b) and _{H} D
−α
a
^{+}
_{,}
_{µ} f ∈ AC
n
δ;
_{µ} [a,
H
D ^{β}
−α a ^{+} , µ ^{H} ^{D} a ^{+}
_{,}
_{µ} f(x) = _{H} D
(β−α) a ^{+} , µ
f
(x).
In particular, if β = n, then
H
D
n
a ^{+} , µ H ^{D} a ^{+}
−α
_{,}
_{µ} f(x) = _{H} D
(n−α) a ^{+} , µ
f
(x).
(31)
(32)
Proof. Combining deﬁnitions of Hadamardtype fractional integral (1) and derivative (2) with
Lemma 1, we have
H D
β
a ^{+} , µ ^{H} ^{D} a ^{+}
−α
_{,} _{µ} f(x)
=
=
x ^{−}^{µ} δ ^{n} x ^{µ} ( _{H} D
x ^{−}^{µ} δ ^{n} x ^{µ} ( _{H} D
−(n−β) a ^{+} , µ
−(n+α−β) a ^{+} , µ
H D
−α
a
_{,}
^{+}
_{µ} f (x))
f (x))
(33)
The inner term of (33) can be formulated as follows.
x ^{−}^{µ} δ · δ ^{n}^{−}^{1} x ^{µ} ( _{H} D
−(n+α−β) a ^{+} , µ
=
f (x)).
_{δ} n−1 _{x} µ _{(} H _{D}
−(n+α−β) a ^{+} , µ
f (x))
_{=}
_{δ} n−1 ^{}
Γ(n + α − β) x
1
a
t ^{µ}
× log ^{x}
t
^{} n+α−β−1 f(t) _{d}_{t}
t
(n + α − β − 1)(n + α − β − 2)
··· (n + α − β − (n − 1))
=
=
Γ(n + α − β)
× x t ^{µ} log ^{x} ^{α}^{−}^{β}
a
t
f(t) ^{d}^{t}
t
Γ(1 + α − β) x
x µ
a
× _{x} µ log ^{x}
t
t
^{} (1+α−β)−1 f(t) _{d}_{t}
t
(34)
Substituting the above term into (33) and taking (2) into account, we obtain
x ^{µ} _{H} D
−(1+α−β)
a ^{+} , µ
=
f (x).
H
D ^{β}
a ^{+} , µ ^{H} ^{D} a ^{+}
−α
_{,}
_{µ} f(x)
=
x ^{−}^{µ} δx ^{µ} ( _{H} D
−(1+α−β)
a ^{+} ,µ
f
(x))
= H D
(β−α) a ^{+} , µ
f (x).
(35)
17500335
on 05/11/17. For personal use only.
^{f}^{r}^{o}^{m} ^{w}^{w}^{w}^{.}^{w}^{o}^{r}^{l}^{d}^{s}^{c}^{i}^{e}^{n}^{t}^{i}^{f}^{i}^{c}^{.}^{c}^{o}^{m}
PITTSBURGH
^{D}^{o}^{w}^{n}^{l}^{o}^{a}^{d}^{e}^{d}
OF
^{F}^{r}^{a}^{c}^{t}^{a}^{l}^{s}
by UNIVERSITY
L. Ma & C. P. Li
15,
and
. Besides, the
_{µ} [a, b] ensures that
_{a} ^{+} _{,} _{µ} f ) exists almost everywhere on
[a, b], which has also been proved in Ref. 15. Thus, this theorem is proved.
If
_{µ} (·),
the
µ
≥
c,
then by Theorem
_{H} D
−α
a
^{+}
_{,}
_{H} D
2.1
in Ref.
(·),
−(1+α−β)
a ^{+} , µ
p
H
D
operators 

−(n+α−β) 
(·) 
a ^{+} , µ 
condition _{H} D
H
D ^{β}
a ^{+} , µ ^{(} ^{H} ^{D}
are bounded in X
−α
a
^{+}
_{,}
−α
_{µ} f
∈
AC
n
δ;
c
If the diﬀerence between α and β is bigger than one, then we have
Theorem 2. Let n − 1 < α ≤ n ≤ m − 1 < β ≤
m, n, m ∈ Z ^{+} , 1 ≤ p ≤ ∞, 0 ≤ a<b ≤ ∞ and let
p (a, b) and
µ, c ∈ R with µ ≥ c. Then for f ∈ X
_{µ} [a, b] there holds
c
H
D
−α
a
^{+}
_{,}
_{µ} f ∈ AC
m
δ;
H
D
β
a ^{+} , µ ^{H} ^{D} a ^{+}
−α
_{,}
_{µ} f(x) = _{H} D
(β−α) a ^{+} , µ
f
(x).
(36)
In particular, if β = m, then
H
D
m
a ^{+} , µ H ^{D}
−α
_{,}
a
^{+}
_{µ} f(x) = _{H} D
(m−α) a ^{+} , µ
f
(x).
(37)
The main idea of this proof is identical
with that of Theorem 1. So we just present a gen
eral sketch of the proof here. First of all, we should observe the variation of β − α. From the condition n − 1 < α ≤ n ≤ m − 1 < β ≤ m, n, m ∈ Z ^{+} ,
we get m − n − 1
is [β − α] = m − n + 1, or [β − α] = m − n, or [β − α] = m − n − 1, where [θ] is the smallest integer which is bigger than θ. Without loss of generality, we only discuss the case when [β − α] = m − n.
m − n + 1, that
Proof.
<
β − α
≤
H
D ^{β}
a ^{+} , µ ^{H} ^{D} a ^{+}
−α
_{,}
_{µ} f(x)
=
x ^{−}^{µ} δ ^{m} x ^{µ} ( _{H} D
−(m+α−β) a ^{+} , µ
f (x)),
f (x)). (38)
Employing the similar technique used in Theorem 1, we can obtain
= x ^{−}^{µ} δ ^{m}^{−}^{n} · δ ^{n} x ^{µ} ( _{H} D
−(m+α−β)
a ^{+} ,µ
δ ^{n} x ^{µ} ( _{H} D
−(m+α−β) a ^{+} , µ
f (x))
= x ^{µ} _{H} D
−((m−n)−(β−α)) a ^{+} , µ
f (x).
(39)
In the presence of the conditions f ∈ X
−α
a
^{+}
_{,}
m
δ;
c
(a, b)
_{µ} [a, b], we substitute (39) into
p
_{µ} f ∈ AC
and _{H} D
(38), then we ﬁnish this proof.
By exchange of the two operators, we can con clude a more general theorem than Lemma 2.35 of Ref. 2.
Theorem 3. Let β ≥ α > 0, n − 1 < α ≤ n ∈
Z ^{+} , m − 1
1 ≤ p ≤ ∞ and let µ, c ∈ R with µ ≥ c. Then
<
β
≤
m
∈
Z ^{+} ,0
≤ a<b
≤
∞,
p
for f ∈ AC _{δ}_{;} _{µ} [a, b] and _{H} D ^{α} _{+} _{,} _{µ} f ∈ X _{c} (a, b), there
n
a
holds
H D
−β
a ^{+} , µ ^{H} ^{D}
_{a} _{+} _{,} _{µ} f(x) = _{H} D
α
−(β−α) a ^{+} , µ
f (x).
Mult mai mult decât documente.
Descoperiți tot ce are Scribd de oferit, inclusiv cărți și cărți audio de la editori majori.
Anulați oricând.